2023
DOI: 10.1177/14574969231167781
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of postoperative pancreatic fistula and pancreatitis after pancreatoduodenectomy or distal pancreatectomy: A review

Abstract: Background and objective: Postoperative pancreatic fistula (POPF) is the leading cause of morbidity and early mortality in patients undergoing pancreatic resection. In addition, recent studies have identified postoperative acute pancreatitis (POAP) as an independent contributor to morbidity. Most perioperative mitigation strategies experimented for POPF have been shown to be in vain with no consensus on the best perioperative management. Clinical prediction models have been developed with the hope of identifyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…Numerous risk factors have been identified in association with POPF (Table 1 ), leading to the development of several prediction models based on these factors. The risk factors can be described in three groups: preoperative, intraoperative, and postoperative factors[ 11 ]. It’s important to note that the risk factors of POPF may vary depending on the type of pancreatic resection being performed[ 12 ].…”
Section: Risk Factors Of Popfmentioning
confidence: 99%
“…Numerous risk factors have been identified in association with POPF (Table 1 ), leading to the development of several prediction models based on these factors. The risk factors can be described in three groups: preoperative, intraoperative, and postoperative factors[ 11 ]. It’s important to note that the risk factors of POPF may vary depending on the type of pancreatic resection being performed[ 12 ].…”
Section: Risk Factors Of Popfmentioning
confidence: 99%
“…Several risk factors have been associated with the development of POPF, which may be related to the type of surgical procedure, type of pancreatic lesion, postoperative course, and patient characteristics [58] , [59] . Recent studies attempted to correlate imaging findings observed on preoperative contrast-enhanced CT with the occurrence of POPF, based on either pancreatic parenchymal findings or the patient body composition.…”
Section: Post-operative Pancreatic Fistulamentioning
confidence: 99%
“…If the author combined the above 2 viewpoints with the prediction of postoperative serum hyperamylasemia and postoperative acute pancreatitis to explore FRS, it will be more meaningful. 4 Finally, we would like to thank the authors again for their contribution. This study provides a more comprehensive and logically rigorous guide for the exploration of FRS, which is of great significance.…”
mentioning
confidence: 97%